EGMR 21881/20 vom 27. November 2023 , CASE OF COMMUNAUTÉ GENEVOISE D'ACTION SYNDICALE (CGAS) v. SWITZERLAND - Hudoc Ch (2023)
Preliminary objection allowed (Art. 35) Admissibility criteria;(Art. 35-1) Exhaustion of domestic remedies;Remainder inadmissible (Art. 35) Admissibility criteria;(Art. 35-1) Exhaustion of domestic remedies;(Art 35-1) Four-month period (former six-month)